2017
DOI: 10.1186/s12889-017-4247-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-related factors that explain disaster-induced changes in socioeconomic status and poor subjective health: a cross-sectional study from the Fukushima health management survey

Abstract: BackgroundSocioeconomic status (SES) and lifestyle-related factors are determinants of subjective health. However, changes in SES are inevitable in times of natural disaster, while lifestyle-related factors remain modifiable. The aim of this study was to use a cross-sectional approach to examine lifestyle-related factors that may attenuate the negative impact of disaster-induced changes in SES on poor subjective health.MethodsWe analyzed 33,350 men and women aged 20–64 years who were living in evacuation zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…We sent a self-administered questionnaire on various lifestyle and mental health factors to all the residents. The overall response rate of the Mental health and lifestyle Survey was 40.7% [14].…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sent a self-administered questionnaire on various lifestyle and mental health factors to all the residents. The overall response rate of the Mental health and lifestyle Survey was 40.7% [14].…”
Section: Subjectsmentioning
confidence: 99%
“…The evacuees experienced not only the earthquake itself but also a tsunami and/or the indirect effects of a nuclear power plant accident. These disasters and experiences affected their living environment, relatives and friends, and socioeconomic status [13,14]. There were also some changes seen between the pre-and post-disaster phases in lifestyle status among evacuees; for example, smoking, drinking, and physical activities [15] as well as psychological distress [16].…”
Section: Introductionmentioning
confidence: 99%
“…The evacuees experienced not only the earthquake itself but also a tsunami and/or the indirect effects of a nuclear power plant accident. These disasters and experiences affected their living environment, relatives and friends, and socioeconomic status [15,16]. There were also some changes seen between the pre-and post-disaster phases in lifestyle status among evacuees; for example, smoking, drinking, and physical activities [17] as well as psychological distress [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, advanced age impacts willingness to bear out-of-pocket checkup expenses [ 14 ], while lack of money, time, and related knowledge prevents people from utilizing cancer screening [ 15 ]. Nagai et al reported that changes of socioeconomic status and community activities were associated with subjective perceptions of health [ 17 ].…”
Section: Introductionmentioning
confidence: 99%